Evaluating diffusion‐weighted magnetic resonance imaging for target volume delineation in head and neck radiotherapy. Issue 3 (28th February 2019) - Cardoso, Michael; Min, Myo; Jameson, Michael; Tang, Simon; Rumley, Christopher; Fowler, Allan; Estall, Vanessa; Pogson, Elise; Holloway, Lois; Forstner, Dion
Abstract: Introduction: Inter‐observer variability (IOV) in target volume delineation is a source of error in head and neck radiotherapy. Diffusion‐weighted imaging (DWI) has been shown to be useful in detecting recurrent head and neck cancer. This study aims to determine whether DWI improves target volume delineation and IOV. Methods: Four radiation oncologists delineated the gross tumour volume (GTV) for ten head and neck cancer patients. Delineation was performed on CT alone as well as fused image sets which incorporated fluorodeoxyglucose (FDG)‐positron emission tomography (PET) and magnetic resonance imaging (MRI) in the form of CT/PET, CT/PET/T2W and CT/PET/T2W/DWI image sets. Analysis of the variability of contour volumes was completed by comparison to the simultaneous truth and performance level estimation (STAPLE) volumes. The DICE Similarity Coefficient (DSC) and other IOV metrics for each observer's contour were compared to the STAPLE for each patient and image dataset. A DWI usability scoresheet for delineation was completed. Results: The CT/PET/T2W/DWI mean GTV volume of 13.37 (10.35–16.39)cm 3 was shown to be different to the mean GTV of 10.92 (8.32–13.51)cm 3 when using CT alone ( P  <   0.001). The GTV DSC amongst observers for CT alone was 0.72 (0.65–0.79), CT/PET was 0.73 (0.67–0.80), CT/PET/T2W was 0.71 (0.64–0.77) and CT/PET/T2W/DWI was 0.69 (0.61–0.75). Conclusion: Mean GTVs with the addition of DWI had slightly larger volumes compared to standard CT and CT/PET volumes. DWI may add supplemental visual information for GTV delineation while having a small impact on IOV, therefore potentially improving target volume delineation.